Xanthomonas campestris pv. campestris에 의한 브로콜리의 검은썩음병 - 나동수(Dong-Soo Ra); 허성기(Sunggi Heu); 이용훈(Yong-Hoon Lee); 김용기(Yong-Ki Kim); 김선이(Sun Yee Kim); 이정희(Junghee Lee); 이승돈(Seungdon Lee) (Sigmulbyeong yeon'gu, 2006)
A new bacterial disease of broccoli (Brassica oleracea var. italica) was observed on field-grown plants in Pyungchang during 2003 and 2004. Seedling infections first appeared as a blackening along the margins of the cotyledon. Cotyledon shriveled and dropped off. Infected seedlings were stunted and yellowed and eventually died. The disease was easily recognized by the presence of yellow, V-shaped, or U-shaped areas extending inward from margin of the leaf. As the disease progressed, the yellow lesions turned brown and the tissues died. Isolations made from diseased leaves on yeast extract dextrose calcium carbonate agar yielded nearly pure cultures of a yellow-pigmented bacterium typical of a xanthomonad. Two bacterial strains were purified and used for further tests. Pathogenicity of strains was confirmed on 3-week-old crucifer (cabbage, Chinese cabbage, kale, radish and broccoli) plants cut by scissors with bacterial suspensions containing $10^8 cfu/ml$ of phosphate buffered saline. The Biolog and fatty acid analyses and 16S rDNA sequencing of two strains (SL4797 and SL4800) from broccoli black rot showed that they could be identified as X. campestris pv. campestris because of their high similarity to the tester strain (X. campestris pv. campestris NCPPB528) with a match probability of 100%. This is the first report of black rot of broccoli in Korea. 2003년부터 2004년 평창 지역의 브로콜리 포장에서 새로운 병해가 발견되었다. 유묘 감염이 되었을 때 떡잎의 주위로부터 검게 변색되기 시작하여 결국 떡잎이 떨어지고 유묘는 죽었다. 성체에서는 잎 가장자리로부터 엽맥을 타고 진전되어 V 자 또는 U 자형의 노란색 병반을 형성하였다. YDC 배지에서 병원세균을 순수 분리하였을 때 Xanthomonas 속 세균의 전형적인 특정인 노란색 색소를 띤 세균이 형성되었다. 분리된 세균을 $10^8 cfu/ml$로 현탁 한후 3 주 동안 자란 브로콜리, 양배추, 배추, 케일, 무에 가위 접종하여 병원성을 확인하였다. 지방산 조성 및 함량, 다양한 탄소원 이용정도 및 16S rDNA 염기서열를 이용하여 분리세균 SL4797 과 SL4800 을 대조균주 X. campestris pv. campestris NCPPB528 과 비교하였을 때 매우 유사하였다. 이 논문은 국내에서 브로콜리의 검은썩음병 최초 보고이다.